The Combination of the CDK4/6 Inhibitor, Palbociclib, With the Vitamin D3 Analog, Inecalcitol, Has Potent In Vitro and In Vivo Anticancer Effects in Hormone-Sensitive Breast Cancer, But Has a More Limited Effect in Triple-Negative Breast Cancer - Vanhevel, Justine; Verlinden, Lieve; Loopmans, Shauni; Doms, Stefanie; Janssens, Iris; Bevers, Sien; Stegen, Steve; Wildiers, Hans; Verstuyf, Annemieke (Frontiers in Endocrinology, 2022)
Active vitamin D3, 1,25-dihydroxyvitamin D3 [1,25(OH)2D3], and its synthetically derived analogs possess potent anticancer properties. In breast cancer (BC) cells, 1,25(OH)2D3 blocks cell proliferation and induces apoptosis through different cell-type specific mechanisms. In this study, we evaluated if the combination of the potent vitamin D3 analog, inecalcitol, with a selective CDK4/6 inhibitor, palbociclib, enhanced the antiproliferative effects of both single compounds in hormone-sensitive (ER+) BC, for which palbociclib treatment is already approved, but also in triple-negative BC (TNBC). Inecalcitol and palbociclib combination treatment decreased cell proliferation in both ER+ (T47D-MCF7) and TNBC (BT20-HCC1143-Hs578T) cells, with a more pronounced antiproliferative effect in the former. In ER+ BC cells, the combination therapy downregulated cell cycle regulatory proteins (p)-Rb and (p)-CDK2 and blocked G1-S phase transition of the cell cycle. Combination treatment upregulated p-mTOR and p-4E-BP1 protein expression in MCF7 cells, whereas it suppressed expression of these proteins in BT20 cells. Cell survival was decreased after inecalcitol treatment either alone or combined in MCF7 cells. Interestingly, the combination therapy upregulated mitochondrial ROS and mitotracker staining in both cell lines. Furthermore, in vivo validation in a MCF7 cell line-derived xenograft mouse model decreased tumor growth and cell cycle progression after combination therapy, but not in a TNBC BT20 cell line-derived xenograft model. In conclusion, we show that addition of a potent vitamin D3 analog to selective CDK4/6 inhibitor treatment results in increased antiproliferative effects in ER+ BC both in vitro and in vivo.